The Lichtheim disease: A rare manifestation of pernicious anemia (Indian Journal of Child Health, 2022)
Subacute combined degeneration of the spinal cord (SACD) is an important neurological complication of vitamin B12 deficiency. It is an important treatable cause of progressive neurological disability. We report a case of a 12-year-old girl, which presented with features of SACD of the spinal cord with low vitamin B12 levels and positive anti-parietal cell antibodies, suggesting vitamin B12 deficiency due to autoimmune etiology. The girl was started on a regimen of intramuscular vitamin B12 treatment. After which she had complete neurological recovery. She was advised of lifelong supplementation of parenteral vitamin B12 due to the autoimmune etiology.